Dynamic Transformation During the Simulated Hot Rolling of an API‐X80 Steel. Issue 8 (16th May 2019) - Mendes‐Fonseca, Nizia; Rodrigues, Samuel F.; Guo, Baoqi; Jonas, John J.
Abstract : The occurrence of dynamic transformation is investigated during the simulated hot rolling of an API‐X80 steel. Torsion tests are carried out under continuous cooling conditions, with all deformation passes applied above the equilibrium transformation temperature. Three different interpass times are investigated: 1, 8, and 20 s. Samples are water‐quenched before and after the odd‐numbered passes, and the volume fraction of ferrite is evaluated metallographically. Dynamic transformation took place under all conditions and the volume fraction of retained ferrite increased with the retained strain. The increase in flow stress during simulated rolling is less than expected under all conditions, which is evidence for the dynamic formation of ferrite. The driving forces and energies barriers are evaluated, indicating that dynamic transformation is mechanically activated. Abstract : The occurrence of dynamic transformation is investigated during the simulated hot rolling. Metallographic analysis shows that ferrite can be formed dynamically during hot rolling when this is carried out above the transformation temperature. Due to the dynamic formation of ferrite, the increase in flow stress is less than expected. Thermodynamic calculations show that this phenomenon is likely to occur.